Meningkatkan Pertumbuhan dan Produksi Sawi Hijau (Brassica juncea L.) melalui Optimalisasi Perendaman Benih dalam Larutan PGPR serta Penerapan Dosis Pupuk NPK - Haris, Abdul; Suherah, Suherah; Akbar, Abdul; Alfirayanti, Alfirayanti (AGRICA, 2024)
This study aimed to evaluate the effect of seed soaking duration in Plant Growth Promotion Rhizobacteria (PGPR) solution and NPK fertilizer dosage on the growth of mustard greens (Brassica juncea L.). The research was conducted from April to May 2024 in Takalar Regency, South Sulawesi. A Randomized Block Design (RBD) with a factorial pattern of two factors was used, namely the duration of seed soaking in the PGPR solution and the dosage of NPK fertilizer. The results showed that the duration of seed soaking in the PGPR solution significantly influenced germination, with a 15-minute soaking period yielding the best results, achieving a germination rate of 99.98%. Additionally, the combination of seed soaking duration and NPK fertilizer dosage also affected plant height and yield.